PPARα Is Required for PPARδ Action in Regulation of Body Weight and Hepatic Steatosis in Mice - Wojciech G. Garbacz; Jeffrey T. J. Huang; Larry G. Higgins; Walter Wahli; Colin N. A. Palmer (PPAR Research)
Peroxisome proliferator activated receptors alpha (PPARα) and delta (PPARδ) belong to the nuclear receptor superfamily. PPARα is a target of well established lipid-lowering drugs. PPARδ (also known as PPARβ/δ) has been investigated as a promising antidiabetic drug target; however, the evidence in the literature on PPARδ effect on hepatic lipid metabolism is inconsistent. Mice conditionally expressing human PPARδ demonstrated pronounced weight loss and promoted hepatic steatosis when treated with GW501516 (PPARδ-agonist) when compared to wild type mice. This effect was completely absent in mice with either a dominant negative form of PPARδ or deletion of the DNA binding domain of PPARδ. This confirmed the absolute requirement for PPARδ in the physiological actions of GW501516 and confirmed the potential utility against the human form of this receptor. Surprisingly the genetic deletion of PPARα also abrogated the effect of GW501516 in terms of both weight loss and hepatic lipid accumulation. Also the levels of the PPARα endogenous agonist 16:0/18:1-GPC were shown to be modulated by PPARδ in wild type mice. Our results show that both PPARδ and PPARα receptors are essential for GW501516-driven adipose tissue reduction and subsequently hepatic steatosis, with PPARα working downstream of PPARδ.